System architecture and key technologies of emergency command Internet of things - Qianbin CHEN; Guojun LI; Guoquan LI; Changrong YE (物联网学报)
Emergency command Internet of things is an important part of the construction of smart cities.It is one of the application fields of the Internet of things,which benefits a wide range,require rich support technologies,drives the whole industry and has large demonstration effect of service.Starting from the construction of the disaster site rescue situation map,the emergency rescue command and command issue at the emergency incident site was focused.Referring to the joint search and rescue network in the battlefield and the tactical Internet system structure,the emergency command Internet of things system architecture was proposed,including body LAN,on-site command network and remote access network.The four key problems faced by the construction of emergency command the Internet of things was discussed,single soldier tracking and positioning,wearable vital signs monitoring,mobile self-organizing network and shortwave sky wave remote communication.The two scenarios of urban fire rescue and natural disaster rescue were used to analyze and design the integrated application system of the emergency command IoT system,which provided useful exploration for building a new generation of emergency command information system and promoting the construction of smart cities.